2013
DOI: 10.1088/0268-1242/28/6/065001
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst and processing effects on metal-assisted chemical etching for the production of highly porous GaN

Abstract: Metal-assisted chemical etching is a facile method to produce micro-/nanostructures in the near-surface region of gallium nitride (GaN) and other semiconductors. Detailed studies of the production of porous GaN (PGaN) using different metal catalysts and GaN doping conditions have been performed in order to understand the mechanism by which metal-assisted chemical etching is accomplished in GaN. Patterned catalysts show increasing metal-assisted chemical etching activity to n-GaN in the order Ag < Au < Ir < Pt.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…Indeed, it has been suggested that the type of transport barrier at the metal/semiconductor interface (i.e., Schottky or Ohmic) will control the charge transfer and hence the MacEtch process3436373839. On perusal, this appears to be true.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it has been suggested that the type of transport barrier at the metal/semiconductor interface (i.e., Schottky or Ohmic) will control the charge transfer and hence the MacEtch process3436373839. On perusal, this appears to be true.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that doping type changes the etch rate with identical Au pattern feature sizes indicates that charge transport, instead of mass transport, is the rate determining factor. It has been reported that the Schottky barrier height, which can be affected by the metal work function, thickness, and size, as well as the semiconductor doping type and level, can affect the etch rate, with faster etch rates for ntype GaN 40 and thicker Au for p-type Si. 41 The Schottky barrier height analysis used in the case of GaN 40 cannot explain the doping type dependence observed in the current study, possibly because the etching condition that is low in oxidant concentration makes the majority carrier transport in the semiconductor play a dominant role in determining the etch rate.…”
Section: Resultsmentioning
confidence: 99%
“…Very long NWs (>10 μm) with a wurtzite structure were obtained. Geng et al [ 38 ] investigated the growth of porous GaN in various metal catalysts and GaN doping environments and demonstrated an improvement in the MacEtch technique and the catalytic scheme in the order of Ag < Au < Ir < Pt. The authors also observed that the catalytic action of continuous films contrasted with that of films with discontinuous islands.…”
Section: Synthesis Methods For (In)gan Nanostructuresmentioning
confidence: 99%
“…MacEtch is the most popular technique because it produces a homogeneous porous morphology over a wide region and is simpler than other surface-roughening techniques. [ 38 , 39 ]. MacEtch prevents the surface damage caused by dry etching procedures, which is desired for potential optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation